2010
DOI: 10.1158/1541-7786.mcr-10-0008
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Induces Proliferation and Migration of Human Prostate Androgen–Independent Cancer Cells by an ABCA1-Dependent Mechanism

Abstract: Androgen deprivation therapy for prostate cancer leads to a significant increase of high-density lipoprotein (HDL), which is generally viewed as beneficial, particularly for cardiovascular disease, but the effect of HDL on prostate cancer is unknown. In this study, we investigated the effect of HDL on prostate cancer cell proliferation, migration, intracellular cholesterol levels, and the role of cholesterol transporters, namely ABCA1, ABCG1, and SR-BI in these processes. HDL induced cell proliferation and mig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 46 publications
(54 reference statements)
6
50
2
Order By: Relevance
“…This correlates with in vivo findings, including reduced ABCA1 expression when hypogonodal (androgen-deficient) mice were treated with testosterone (49), increased ABCA1/G1 expression in PCa xenografts when mice were treated with the androgen synthesis inhibitor dutasteride (50), and increased ABCA1 mRNA levels in PCa tissues from patients receiving androgen deprivation therapy (38). Thus, the cross-talk between AR and LXR is observed in vivo and hence has biological relevance.…”
Section: Discussionsupporting
confidence: 75%
“…This correlates with in vivo findings, including reduced ABCA1 expression when hypogonodal (androgen-deficient) mice were treated with testosterone (49), increased ABCA1/G1 expression in PCa xenografts when mice were treated with the androgen synthesis inhibitor dutasteride (50), and increased ABCA1 mRNA levels in PCa tissues from patients receiving androgen deprivation therapy (38). Thus, the cross-talk between AR and LXR is observed in vivo and hence has biological relevance.…”
Section: Discussionsupporting
confidence: 75%
“…32 One study identified a set of genes that might act to promote lung cancer metastasis, reporting that the expression of these genes depends on MALAT1. [34][35][36][37] These MALAT1 target genes were either associated with metastasis or represented critical regulators of metastasis establishment, and were strongly reduced by the loss of MALAT1. 34 These reports support the hypothesis that MALAT1 is an activator of metastasis and affects metastatic processes.…”
Section: Malat1-prc1 Pathwaymentioning
confidence: 99%
“…HDL, which is generally viewed as beneficial, particularly for cardiovascular disease, but the effect of HDL on prostate cancer is unknown [15].…”
Section: Discussionmentioning
confidence: 99%
“…HDL by an ABCA1-dependent mechanism can mediate signal transduction, leading to increased proliferation and migration of prostate cancer cells. [15].…”
Section: Cancer Patients Normal Subjectsmentioning
confidence: 99%